Lean Six Sigma in the public sector: yesterday, today and tomorrow. (3rd April 2021) - Rodgers, Bryan; Antony, Jiju; Edgeman, Rick; Cudney, Elizabeth A.
Abstract : This paper draws on recent work which explores the subject of Lean Six Sigma from both an academic and practitioner view. A similar framework is utilised to explore the state of Lean Six Sigma in the public sector from its earliest published origins through the current thinking to develop thoughts on some challenges for the future. The authors also draw on data from a systematic literature review on the subject and their own extensive experience of Lean Six Sigma and the public sector across two continents.